2008
DOI: 10.1007/s10620-008-0590-6
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of Circulating CD4+CD25high T Cells in Naïve Crohn’s Disease

Abstract: Crohn's disease is considered to be caused either by an excess of T-cell effector functions and/or by a defective regulatory T-cell compartment. The aim of this study was to assess in Crohn's disease the frequency of circulating CD4(+)CD25(high) T cells that possess regulatory T-cell functions and CD4(+)CD25(low) T cells that contain activated T cells. Flow cytometry of peripheral blood was used to assess CD4(+)CD25(high) and CD4(+)CD25(low) T-cell frequencies in a cohort of 66 patients with Crohn's disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Indeed, CD4 þ and CD8 þ T-cell increase in PP was observed in a mouse model for CD and an increase in both CD4 þ and CD8 þ T cells was reported in patients with active CD, whereas the Treg population was lowered. [45][46][47] Also, the combination of smoke-induced apoptosis with other proapoptotic factors, such as the proinflammatory cytokine TNF-a, can account for a misbalance between immune defence and tolerance. 48 Once this imbalance reaches a threshold, tolerance to oral antigens is lost, resulting in an uncontrolled immune response and intestinal inflammation.…”
Section: Smoking Alters Intestinal Apoptosis and Galtmentioning
confidence: 99%
“…Indeed, CD4 þ and CD8 þ T-cell increase in PP was observed in a mouse model for CD and an increase in both CD4 þ and CD8 þ T cells was reported in patients with active CD, whereas the Treg population was lowered. [45][46][47] Also, the combination of smoke-induced apoptosis with other proapoptotic factors, such as the proinflammatory cytokine TNF-a, can account for a misbalance between immune defence and tolerance. 48 Once this imbalance reaches a threshold, tolerance to oral antigens is lost, resulting in an uncontrolled immune response and intestinal inflammation.…”
Section: Smoking Alters Intestinal Apoptosis and Galtmentioning
confidence: 99%
“…Pioneering studies by Powrie and colleagues demonstrated that the pathology in a mouse model of T cell-induced colitis, which mimics human inflammatory bowel disease (IBD), can be prevented by adoptive transfer of Foxp3 þ Treg (4). The number of Treg is lower in the peripheral blood of patients with active IBD than in that of control subjects (5). Conversely, the number of Treg is higher in the intestinal mucosa of patients with IBD, and their function is normal, as demonstrated by their ability to suppress the proliferation of effector cells in vitro (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, these cells were lacking in the peripheral blood of patients with the active disease, when compared to those who were in the inactive phase or in the control group [8385]. For Tregs to be functional, a signal made by TGF- β is needed.…”
Section: T Regulatory Cellsmentioning
confidence: 99%